Pediatric otorhinolaryngology diagnosis and treatment - Licameli, Greg R.; Tunkel, David E. (Thieme, 2013)
Pediatric Otorhinolaryngology: Diagnosis and Treatment addresses the medical and surgical treatment of the most common and challenging clinical conditions in the rapidly growing field of pediatric otorhinolaryngology. Clear, concise chapters distill a significant amount of information that the pediatric subspecialist will find useful to reference in daily practice. Residents will also find this text valuable as a guide during pediatric otorhinolaryngology rotations.